Inovasi Pelayanan Publik Berbasis Android ‘Paga Nagari’ Di Polres Solok Kota - Eriza, Aranzi; Yoserizal, Yoserizal; Ekha Putera, Roni (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2021)
The police institution has the duty and responsibility to provide services to the community relating to security and other services to citizens. One way to improve service quality is to innovate services. So the focus of this research is on the implementation of Android-based public service innovation through an application feature called 'Paga Nagari' on the Solok City Police Station. Based on the identification results obtained by researchers, 'Paga Nagari' is the latest innovation from Solok City Regional Police that utilizes internet technology. Solok City Police Station is the only Polres in West Sumatra that utilizes internet technology to provide complete services to the public such as the existence of Panic Button, complaints, making online SIM, online SKCK, Certificate of Loss, Notification of Progress of Investigation (SP2HP) ), Crowd Permit, Security Assistance and Escort Request. Then an in-depth study is needed on how the Solok City District Police will carry out the ‘Paga Nagari’. The research method chosen was a descriptive qualitative approach. This research uses Rogers' theory in Suwarno (2008: 17), which measures the innovation attribute variable with five things, namely relative advantages, compatibility, complexity (complexity); the possibility of being tried (liability; and observability. Based on the results of the study, the service at the Solok City Police Station through the innovation based on the android application 'Paga Nagari' is already excellent. However, these efforts have not yet run optimally, obstacles are still often faced by Solok Kota Police and the community as users, especially in terms of networks and non-intensive socialization